Pendampingan Kepala Sekolah dalam Pengembangan Supervisi Akademik melalui Bimbingan Pelatihan di Era Kurikulum Merdeka - Suroso, Suroso (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This paper aims to present a structured plan to support school principals in developing academic supervision programs through targeted training in the